(untitled) (Homoeopathy for All, 2022)
People with the tendency of hyperacidity possibly have some link with psychology either external, internal, or both. The basic nature of the person or his reaction to the external stimuli reflects in the form of hyperacidity in many cases. Studies found that psychosocial stress is associated with the exacerbation of symptoms in several functional disorders of the gastrointestinal (GI) tract. 1,2 Heartburn and acidity are common symptoms ofmany gastrointestinal disorders. Gastroesophageal reflux disease (GERD) is one of the most common conditions with heartburn and hyperacidity. There is a multifaceted interaction between GERD, patient-perceived symptoms, and psycho-emotional states. Shreds of evidence exist on the effects of stress on oesophageal and stomach function. GERD may cause anxiety and depressive symptoms. 3 Psychological comorbidity is also very common with these conditions. 4 Homoeopathy has drugs based on the individualistic nature of the mental condition or manifestation. Documentation of mental symptoms homoeopathy, from proving to philosophy to the repertory. With the help of repertory, these drugs are utilized effectively in clinical practice. Many main rubrics of main symptoms are with specific individualistic sub-rubrics so that more individualization can be achieved. This article focuses on how the cases of hyperacidity can be approached using psychosomatic analysis.